Descriptive Model of Community Participation: Delivering Urban Services - Abdulraheem, A; Raman, A (Ushus Journal of Business Management, 2005)
Community participation means readiness of both the government and the community to accept certain responsibilities and activities. It also means that the value of each group’s contribution is seen, appreciated, and used more tokenism or propaganda will not make participation meaningful. The honest inclusion of community representative as partners in decision-making makes for successful community participation. Basic urban services in India are inadequate to meet the needs of the population in low-income areas. This is evident from past studies undertaken at both the macro and micro level. Furthermore, the situation will continue unchanged in the future despite government agency efforts to improve the infrastructure and service delivery, as projected capabilities will not meet projected needs for services. There is a need, therefore to extend services through community participation strategies. Community involvement has been sought in the past through certain government projects. Therefore, is a model that will describe an approach to service delivery of a participatory nature? This should be considered not only as an option but also as a recommended approach in future plans for urban development. Therefore, this paper describe that the participatory management model and some policy implication towards community participation.